Answer:
x=8 an they are at the exact opposite side
Step-by-step explanation:
recall in a perfect square trinomial, the middle term is the tale-tell guy, we know the middle term is the product of 2 and the two other guys without the exponent, so in this case 6x = 2*√x² * √c.
![\bf 6x=2\cdot \sqrt{x^2}\cdot \sqrt{c}\implies 6x=2\sqrt{x^2c}\implies 6x=2x\sqrt{c}\\\\\\\cfrac{6x}{2x}=\sqrt{c}\implies 3=\sqrt{c}\implies 3^2=c\implies 9=c](https://tex.z-dn.net/?f=%20%5Cbf%206x%3D2%5Ccdot%20%5Csqrt%7Bx%5E2%7D%5Ccdot%20%5Csqrt%7Bc%7D%5Cimplies%206x%3D2%5Csqrt%7Bx%5E2c%7D%5Cimplies%206x%3D2x%5Csqrt%7Bc%7D%5C%5C%5C%5C%5C%5C%5Ccfrac%7B6x%7D%7B2x%7D%3D%5Csqrt%7Bc%7D%5Cimplies%203%3D%5Csqrt%7Bc%7D%5Cimplies%203%5E2%3Dc%5Cimplies%209%3Dc%20)
Answer:
y = -2x + 8
Step-by-step explanation:
When two points are given, the equation of the line passing through the points is given by:
![$ \frac{y - y_1}{y_2 - y_1} = \frac{x - x_1}{x_2 - x_1} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7By%20-%20y_1%7D%7By_2%20-%20y_1%7D%20%3D%20%5Cfrac%7Bx%20-%20x_1%7D%7Bx_2%20-%20x_1%7D%20%24)
where:
and
are the two points passing through the line.
Here,
and
.
Substituting in the formula, we have:
![$ \frac{y - 4}{2 - 4} = \frac{x - 2}{3 - 2} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7By%20-%204%7D%7B2%20-%204%7D%20%3D%20%5Cfrac%7Bx%20-%202%7D%7B3%20-%202%7D%20%24)
⇒ ![$ \frac{y - 4}{-2} = \frac{x - 2}{1} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7By%20-%204%7D%7B-2%7D%20%3D%20%5Cfrac%7Bx%20-%202%7D%7B1%7D%20%24)
⇒ y - 4 = -2x + 4
⇒ y = -2x + 8 is the required equation of the line.
Answer:
-4,5
Step-by-step explanation: